2022
DOI: 10.35445/alishlah.v14i3.2385
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Satisfaction and Learning Motivation toward Online Learning during the Covid-19 Pandemic

Abstract: This study aimed to examine students’ learning motivation and satisfaction in attending lectures during the Covid-19 pandemic. This descriptive correlational study involved 155 students majoring in Early Childhood Education Teacher Education (PG-PAUD) registered in 2019, who were selected through total sampling technique. Data in this study were obtained by distributing two types of questionnaires (learning satisfaction level questionnaire and learning motivation questionnaire) to all students. Before distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The unexplained part of the motivation can be explained by students' digital education because of COVID-19 pandemic and related variables. 40 In terms of academic self-efficacy score, the academic self-efficacy of the students in our study was above-medium, indicating that they felt their academic self-efficacy partially sufficient, and they needed support. Similar to our study, Croy et al (2020) found medium academic self-efficacy in their study with nursing students.…”
Section: Descriptive Statistics Of Academic Selfefficacy Motivation A...mentioning
confidence: 63%
“…The unexplained part of the motivation can be explained by students' digital education because of COVID-19 pandemic and related variables. 40 In terms of academic self-efficacy score, the academic self-efficacy of the students in our study was above-medium, indicating that they felt their academic self-efficacy partially sufficient, and they needed support. Similar to our study, Croy et al (2020) found medium academic self-efficacy in their study with nursing students.…”
Section: Descriptive Statistics Of Academic Selfefficacy Motivation A...mentioning
confidence: 63%
“…The results show that there is a decrease in student motivation, and it does not satisfy students with the method used by the lecturer. This is supported by the opinion of Mayar et al [30] which states that student motivation and satisfaction in the learning process is determined by the method used by the lecturer. Unpreparedness in facing online learning will affect decreasing student motivation and achievement [31]- [33].…”
Section: E Discussionmentioning
confidence: 82%